The Challenge of Pancasila in the Development of the Millennial Generation - Aimana, Salwa Nadiyah (Jurnal Scientia Indonesia, 2017)
The Indonesian nation has a unifying tool for the nation which is formed from the noble values of Indonesia. In the era of the Majapahit kingdom, in the book Sutasoma by Mpu Tantular it is written "Bhineka Tunggal Ika, Tan Hana Dharma Mangrwa" which tells that at that time there were no disputes caused by differences caused by differences in religion or ethnicity. This proves that respect for differences has been believed by the ancestors of the Indonesian people since hundreds of years ago. Therefore, it is very unfortunate if the history of harmony in the Indonesian nation, which has been hundreds of years, has to be destroyed by hatred caused by greed and the struggle for power by certain groups. In the millennial era, technological developments are far more advanced with various existing developments. Along with the times, information is more easily accessible in various parts of the world. Everyone can access any information from any country with the international system. Everyone cannot avoid technological developments that are always there and change all the time. Communication and information technology has changed conventional wars into modern wars using technology, mass media, the internet and the targets are economic resilience, defense and security, culture, ideology, environment, politics, and character.